Ideological Approaches in Translating Arabic Food Recipes from The Instagram Account @maisinthekitchen - Tawakkila, Rudzika; Hidayatullah, Moch Syarif (Asalibuna, 2025)
Abstract: This study discusses the application of translation ideology in translating Arabic food recipes uploaded by the Instagram account @maisinthekitchen into Indonesian. Recipe texts are rich in cultural elements, requiring translators to adopt an appropriate approach to maintain a balance between the authenticity of the source culture and the readability in the target culture. This research uses a qualitative descriptive approach by applying a combined ideology, namely foreignization and domestication. The data consist of Arabic recipes taken from @maisinthekitchen’s Instagram posts between January and December 2024. The results show that out of 144 data points, 62 (43%) apply the foreignization ideology, while 82 (57%) apply the domestication ideology. This shows that domestication tends to be used more to ensure readability and ease of understanding for the target readers, whereas foreignization is applied selectively to preserve the authenticity of Arabic culinary terms, allowing readers to still gain original cultural insights from the recipe. This study is expected to enrich the field of translation studies, particularly in the context of culinary texts, and provide practical contributions for translators and enthusiasts of Arabic cuisine.   Abstrak:  Penelitian ini membahas penerapan ideologi penerjemahan dalam menerjemahkan resep masakan Arab yang diunggah oleh akun Instagram @maisinthekitchen ke dalam bahasa Indonesia. Resep masakan merupakan teks yang sarat unsur budaya, sehingga penerjemah perlu memilih pendekatan yang tepat untuk menjaga keseimbangan antara keautentikan budaya sumber dan keterbacaan dalam budaya sasaran. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan menerapkan ideologi gabungan, yaitu foreignisasi dan domestikasi. Data berupa resep masakan Arab diambil dari unggahan akun @maisinthekitchen selama periode Januari hingga Desember 2024. Hasil penelitian menunjukkan bahwa dari total 144 data, sebanyak 62 data (43%) menerapkan ideologi foreignisasi dan 82 data (57%) menerapkan ideologi domestikasi. Hal ini menunjukkan bahwa domestikasi cenderung lebih banyak digunakan untuk memastikan keterbacaan dan kemudahan pemahaman bagi pembaca sasaran, sedangkan foreignisasi digunakan secara selektif untuk menjaga autentisitas istilah kuliner Arab, sehingga pembaca tetap memperoleh wawasan budaya asli dari resep tersebut. Penelitian ini diharapkan dapat memperkaya khazanah studi penerjemahan, khususnya dalam konteks teks kuliner, serta memberikan kontribusi praktis bagi para penerjemah dan pecinta kuliner Arab.